Pediatric Acute Respiratory Distress Syndrome (PARDS) On Pediatric COVID-19 Patients - Rahmah, Siti; Wahyu Alfian Muharzami, Lalu; Akhdani Almaesy, Lastri; Nurhayati, Putri; Sasmitha A, Ridha (Jurnal KESANS : Kesehatan dan Sains, 2021)
At the end of 2019, there was a pandemic happening in the world, called the novel Coronavirus disease-19 (COVID-19). Various spectrums of disease from COVID-19, one of which is ARDS. The incidence of COVID-19 in children is not as much as in adults. However, in children under one year of age it can get worse. The main characteristic of worsening infection is the occurrence of ARDS. Objective: To find out the best treatment for PARDS in COVID-19 patients. Method: The writing of this article uses various sources from scientific journals to government guidelines and related institutions. Search articles using the keywords “Acute Respiratory Distress Syndrome”, “ARDS”, “Pediatric Respiratory Distress Syndrome”, “PARDS”, and “PARDS on COVID-19” Result and Discussion: PARDS was defined based on PALICC in 2015. Pathophysiology of PARDS in COVID-19 patients is still unclear. However, there is a theory that explains the way SARS-Cov-2 enters cells, namely through membrane fusion, giving rise to ARDS. The difference in handling PARDS for COVID-19 patients is that the handling technique is more alert to the risk of aerosols. Conclusions: There are differences in the handling of PARDS for COVID-19 patients in the technique by reducing the risk of virus transmission by preventing leakage when using a ventilator and using a bacterial/virus filter, as well as rescuers and staff using complete PPE during the procedure.